Analisis Strategi Marketing Mix dalam Upaya Menarik Minat Pelanggan di Cottage Eco Park Syari’ah Tan Kayo Nagari Malalo Kecamatan Batipuh Selatan Kabupaten Tanah Datar dalam Perspektif Bisnis Islam - Fatimah Balqis Azzahra; Novera Martilova (Transformasi: Journal of Economics and Business Management, 2024)
This research was motivated by the decreasing number of customers at the Eco Park Syariah Tan Kayo cottage and the services and facilities provided were not optimal. The purpose of this research is to analyze the marketing mix strategy implemented by Eco Park Syariah Tan Kayo cottage in an effort to attract customer interest and to analyze the obstacles to the marketing mix strategy implemented by Eco Park Syariah Tan Kayo cottage in attracting customer interest. This type of research is research using a qualitative approach. The primary data source is Cottage Eco Park Syariah Tan Kayo. Secondary data in this research consists of the organizational structure of archival data, documents, reports and other books related to this research. The collected data was then analyzed using descriptive methods. The data collection methods used in this research are literature study, interviews, observation and documentation. The result of this research is that the marketing strategy carried out by Cottage Eco Park Syariah Tan Kayo is by using the 7P marketing mix application which consists of product, price, place, promotion, people, process, and physical evidence that do not conflict with Islamic business law. Cottage Eco Park Syariah Tan Kayo developed a special marketing strategy that is able to attract customer interest by differentiating the facilities and rules that apply so that they are different from other accommodations, besides that customers feel safe and comfortable because they have carried out a muamalah process that is based on sharia and of course avoid adultery because of the strict selection of guests at Cottage Eco Park Syariah Tan Kayo.